ANALISIS PENGUNJUNG DAN RETRIBUSI (PEDAGANG) KAWASAN WISATA RELIGI SUNAN GIRI TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN GRESIK PERIODE 2011-2016 - Muainul Islah; R. Moh. Qudsi Fauzi (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study aims to determine the effect of Number of Visitors and Levies to Local Revenue partially and simultaneously. The sample used in this research is probability sampling that is monthly data of Sunan Giri (X1), Sunan Giri (X2) Retribution from Tourism and Culture Office of Gresik Regency. So that got 72 sample research. This research uses quantitative approach method and using multiple linear regression analysis. The results showed that some of the variable of the number of visitors did not have an effect on the Local Original Income, Retribution of merchants have a significant positive effect on the Original Revenue. Simultaneously variable Number of Visitor and Levy have significant effect to Original Income of Gresik Regency.Keywords: Number of Sunan Giri Religious Tour Visitors, Sunan Giri Tourism Retribution, Gresik District Original Income.REFERENCESAl Qur’an dan terjemahannya. 2005. Syamil Al-Qur’an. Bandung: PT Syamil   Cipta Media.Arby, Ikhsan, 2017. Fakultas  pariwisata Umsb sebagai pusat Pengembangan pendidikan pariwisata syariahAnsori dan Iswati. 2009. Buku Ajar Metodelogi Penelitian Kuantitatif. Surabaya: Airlangga University Press.Halim, Abdul. 2004. Manajemen Keuangan Daerah.Yogyakarta: (UPP) AMP YKPN.Hamjah, N. (2015). Pengaruh Periklanan, Pameran dan Event terhadap peningkatan kesadaran wisatawan dan dampaknya pada minat berkunjung ke destinasi wisata religi di aceh. Jurnal Manajemen, Vol.4, No.2.Mangkoesoebroto, Guritno. 2001. Ekonomi Publik. BPFE, Yogyakarta.Mardiasmo. 2000 .Membangun Manajemen Keuangan Daerah. Andi. Yogyakarta.Munajjed, M. (2010). Hakekat Wisata Dalam Islam, Hukum dan Macam-macamnya. https://islamqa.info/id/87846. Diakses pada tanggal 25 Juli 2017.Pendit, Nyoman S. 2002. Ilmu Pariwisata: Sebuah Pengantar Perdana, Jakarta: Pradnya Paramita. Salim, F.B. (2012). Panduan Wisatawan Muslim. Jakarta: Pustaka Al-Kautsar.Sammeng, Andi, Mappi. 2001. Cakrawala Pariwisata. Jakarta: Balai Pustaka.Samsubar, Saleh. 2003. “Kemampuan Pinjam Daerah Kabupaten dan Kota diIndonesia”, Vol. XIV No. 2 Desember 2003, Semarang: Media Ekonomi & Bisnis.Sutrisno P.H, 1988, Dasar – Dasar Ilmu Keuangan Negara, BPFE, Yogyakarta.Syahriza, R. (2014). Pariwisata Berbasis Syariah (Telaah Makna Kata Sara dan Derivasinya dalam al-Qur’an). Jurnal Human Falah, Vol. 1, No. 2